SOCIO-ECOLOGICAL MINISTRY OF THE RUSSIAN ORTHODOX CHURCH: (END OF THE 19TH-BEGUINNING OF THE 20TH CENTURIES) - E. Lifanova, Tatiana; A. Shilina, Svetlana; Yu. Sycheva, Ekaterina; V. Nozdracheva, Elena; V. Golenkova, Olga (Gênero & Direito, 2020)
The current Russian society is characterized by close attention of the state to the environmental situation, the system of social assistance to the needy, social service and volunteering, as well as preserving the natural environment and maintaining ecological balance. The present study aims to analyze the process of socio-ecological ministry of the Russian Orthodox Church (ROC) in the late 19th – early 20th centuries. The results were obtained using in-depth historical, sociological, and quantitative data analysis (one-dimensional statistical analysis) of the source base: the works of prominent historians of Russia and materials from state archives. The relevance lies in the fact that the materials of the study illustrate the areas of the ministry of the ROC, poorly described in literature. Knowledge of the history of the development of a particular social industry, including the role of the ROC in the development of social charity, is an integral part of any social knowledge.